The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s12038-012-9183-9
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism in pigmentary phenotypes

Abstract: The p53 protein exerts different cellular functions, and recent findings have demonstrated its influence on the cascade of skin pigmentation during UV exposure. Among TP53 gene polymorphisms, the most studied is the G to C transversion in exon 4 at codon 72, which results in three distinct genotypes, Arg/Arg, Pro/Pro and Arg/Pro, each one encoding different p53 isoforms. Therefore, this study aimed to determine the relationship between TP53 codon 72 polymorphism and skin protection against sunburn. Genomic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…These findings are not in line with a recent study of TP53 polymorphism among 96 individuals [36] from a Brazilian population where was found a high prevalence of Arginine allele (68%) showing a contrast to our study where Arginine allele frequency was 38% (19 of 50). However, we did not find an association between p53 genotype and breast cancer development.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are not in line with a recent study of TP53 polymorphism among 96 individuals [36] from a Brazilian population where was found a high prevalence of Arginine allele (68%) showing a contrast to our study where Arginine allele frequency was 38% (19 of 50). However, we did not find an association between p53 genotype and breast cancer development.…”
Section: Discussioncontrasting
confidence: 99%
“…The aforementioned polymorphism, which is the most widely studied polymorphism of TP53, refers to a G to C transversion in exon 4 at codon 72 and results in the three following genotypes: Arginine/Arginine (Arg/Arg), Arginine/Proline (Arg/Pro) and Proline/Proline (Pro/Pro). It has been shown that the Arg allele (major allele) predominates over the Pro allele (13). TP53 is a tumor suppressor protein that is responsible for the maintenance of genome stability and is considered to weaken the migration of cancer cells (14).…”
Section: Introductionmentioning
confidence: 99%